GENESIS OF THE NYURUNDUKAN ULTRAMAFIC-MAFIC PLUTON, BAIKAL MOUNTAIN LAND - Tsygankov A.A.; Filimonov A.V.; Vrublevskaya T.T.; Travkin A.V. (My University, 2002)
Genesis of the Nyurundukan ultramafic-Mafic pluton, Baikal mountain land was discussed. The massif was determined to consist of three intrusive phases, each of which was accompanied dike rocks. The results demonstrated that a melt of phase-II gabbroids composition can be produced by the fractional crystallization of picobasalt that was parental for the first intrusive phase in an intermediate chamber at a pressure of 12 kbar.